The magic school bus gets caught in a web - Lane, Jeanette; Enik, Ted.; Degen, Bruce; Cole, Joanna (New York : Scholastic, 2007)
Ms. Frizzle's class is learning about spiders. They take a trip to meet a spider expert, but she's missing. Then the bus turns into a moth and the class gets a very close look at some spiders and their webs.
"Cartwheel books."
"Based on the 'Magic School Bus' books written by Joanna Cole and illustrated by Bruce Degen"--P. facing t.p.
Keywords: Spiders -- Juvenile fiction; Frizzle, Ms. (Fictitious character) -- Juvenile fiction; Spiders -- Fiction; Frizzle, Ms. (Fictitious character) -- Fiction